Polymer with tetrazolic pendant groups. Interaction between the heterocyclic groups and heavy metals - Grassi, Diego (2013)
The interaction between a polymer with tetrazolic pendant groups, and heavy metals (Pb(II) or Cd(II)) was studied. The product resulting from these interactions was characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry and scanning electron microscopy coupled with an energy dispersive X ray fluorescence. From FT-IR analysis we can conclude that the interaction between tetrazole rings and divalent metals is a combination of N-coordination and salt formation. As results of these interactions 1.3 mmol of Pb(II) or 1.5 mmol of Cd(II) per gram of polymer are removed from aqueous solution. The metals as well as the organic material can be recuperated from the solid by pH shifting; indeed the polymer can be reused.